Review of the nominotypical subgenus of Arachnospila Kincaid (Hymenoptera: Pompilidae) of Russia and neighbouring countries with the lectotypification of enigmatic Pompilus sogdianus Morawitz and description of new species - Lelej, Arkady S.; Loktionov, Valery M. (Zootaxa, 2011)
Eleven species are reviewed. A lectotype of Pompilus sogdianus Morawitz 1893 is designated, illustrated and redescribed. The distribution of Arachnospila sogdiana (Morawitz) is limited to Tajikistan only. A new species from Tajikistan, A. gussakovskii sp. nov., is described and illustrated. A new synonymy is proposed for Pompilus clericalis Morawitz 1893 =Arachnospila mongolorufa Wolf & Móczár 1972, syn. nov. Psammochares subocellatus Haupt 1933 is synonymized with Psammochares effodiens f. quadrimaculata Haupt 1929, syn. nov., which is raised to specific status and removed to Arachnospila. The synonymy of Arachnospila sogdiana koenigsmanni Wolf 1970 with Pompilus sogdianus Morawitz 1893 is confirmed. Pompilus turcorum de Dalla Torre 1897 (=Pompilus vagans Radoszkowski 1877, nom. praeocc., nec Costa 1874) is resurrected and moved to Arachnospila. A key to the species for both sexes is given.